Flow Diversion for the Management of Ruptured Intracranial Arterial Infudibular Dilatation: Proof of Principle and Therapeutic Protocol - Matanov, Svetozar; Sirakova, Kristina; Chupetlovksa, Kalina; Penkov, Marin; Monov, Dimitar; Krupev, Martin; Minkin, Krasimir; Ninov, Kristian; Karakostov, Vasil; Sirakov, Stanimir (Frontiers in Neurology, 2022)
Thought to be benign anatomical variants, cerebral infundibular dilatations (ID) are most commonly encountered at the junction of the internal carotid artery (ICA) and the posterior communicating artery (PcomA). The true nature of this entity remains controversial, as some literature reports suggest they should be considered preaneurysmal lesions and a potential source of devastating subarachnoid hemorrhage. This report describes cases of presumably ruptured IDs and their therapeutic endovascular management. We retrospectively reviewed and analyzed patients with isolated subarachnoid hemorrhage (SAH) where the only potential cause was ruptured cerebral IDs, treated or not, between January 2012 and June 2021. Morphological and radiological features, treatment and procedural considerations, clinical and angiographic outcomes were also reviewed. Natural history of the ID is poorly understood, and its relation to SAH remains controversial. Ruptured cerebral IDs can be the suspected cause of bleeding if no other vascular lesion is present during multimodal examinations. Endovascular flow diversion stenting is safe and effective for the proper treatment of ruptured IDs. Pending further validations with longitudinal data are needed to legitimate the natural course of these mysterious lesions.